2014
DOI: 10.1159/000362928
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, Lifestyle, and Anthropometric Risk Factors for Differentiated Thyroid Cancer in Cuba: A Case-Control Study

Abstract: Background: The incidence of differentiated thyroid carcinoma (DTC) is low in people of African origin and higher in populations living on islands, but there is no well-established explanation for these differences. Cuba is a multiethnic nation with people of African and Spanish descent. Until now, no study on the risk factors of DTC has focused on the Cuban population. Our aim is to establish the role of environmental and lifestyle factors and to relate anthropometric measurements to the risk of developing DT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 18 publications
0
41
0
2
Order By: Relevance
“…A recent case-control study on thyroid cancer risk factors, which has been performed in Cuba [12], has shown that thyroid cancer risk was lower in populations of African origin and increased with parity and BSA. Being rhesus factor positive, having a personal history of benign thyroid disorder, an agricultural occupation and an artesian well as the main source of drinking water were also factors associated with a significantly increased risk of developing DTC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent case-control study on thyroid cancer risk factors, which has been performed in Cuba [12], has shown that thyroid cancer risk was lower in populations of African origin and increased with parity and BSA. Being rhesus factor positive, having a personal history of benign thyroid disorder, an agricultural occupation and an artesian well as the main source of drinking water were also factors associated with a significantly increased risk of developing DTC.…”
Section: Introductionmentioning
confidence: 99%
“…In women, irregular cycles and menopause status were associated with a higher risk of DTC. On the other hand, thyroid cancer risk was lower in current or former smokers than in nonsmokers [12]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En un metaanálisis que incluyó 282,137 pacientes con cáncer, el incremento del IMC fue relacionado con ligeros incrementos en el riesgo de CDCFT. Los riesgos estimados van desde 1.0 hasta 7.4 en mujeres, según estudios publicados [34,50,53].…”
Section: Discussionunclassified
“…En un metaanálisis que incluyó 282,137 pacientes con cáncer, el incremento del IMC fue relacionado con ligeros incrementos en el riesgo de CDCFT. Los riesgos estimados van desde 1.0 hasta 7.4 en mujeres, según estudios publicados [34,50,53].En relación al efecto de la obesidad sobre la agresividad de la enfermedad maligna tiroidea, Kim y col.[45] encontraron fenotipos de carcinoma de tiroides más agresivos, relacionados con el IMC; pero otros autores no han podido demostrar la relación entre obesidad y tasa de recurrencia en el CDCFT [30,54].Los posibles mecanismos implicados en esta relación llevan a varias hipótesis que Pappa y Alevizaki [31] tratan de esclarecer en una revisión sobre el tema.Ellos incluyen por un lado, el efecto que tiene la obesidad sobre la disregulación de la vía mitogénica en presencia de resistencia a la insulina, inflamación y estrés oxidativo, como comunes denominadores; en especial cuando existe una distribución central de la grasa. Pero estos aún no son uniformes y en algunos casos, hasta contradictorios [55,56].…”
unclassified